Fairy tail. 61 - Mashima, Hiro, 1977- (Kodansha Comics, 2017)
As the most powerful wizards of Fairy Tail face off against the remaining members of The Twelve, their hearts, relationships, and skills will be put to the test. The battle between Erza and Irene reaches an emotional conclusion, Gray shows how far he's willing to go to save his dearest friends, and the love of a father sparks a shocking revelation from August. As Natsu and Zeref's showdown approaches, both enemies and friends must ask themselves who their true family is!--Amazon.